2018
DOI: 10.1097/md.0000000000013605
|View full text |Cite
|
Sign up to set email alerts
|

Medial patellofemoral ligament reconstruction in children

Abstract: Background:Many surgical procedures have been described to treat recurrent patellar dislocation, but none of these techniques has been successful in all patients. The goal of the study was to evaluate the results of medial patellofemoral ligament reconstruction in children. Two operative procedures were evaluated; a fascia lata allograft and an autologous gracilis graft.Methods:Forty-four children (27 girls and 17 boys) between 13 and 17 years of age with unilateral recurrent patellar dislocation underwent med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…No further studies were found from manually checking the reference lists of the selected articles. In the end, 12 articles that met all the inclusion criteria were finalized for our study [9][10][11][12][13][14][15][16][17][18][19][20]. The flowchart in Figure 1 depicts the selection process of the studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…No further studies were found from manually checking the reference lists of the selected articles. In the end, 12 articles that met all the inclusion criteria were finalized for our study [9][10][11][12][13][14][15][16][17][18][19][20]. The flowchart in Figure 1 depicts the selection process of the studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Seven studies 4 , 7 , 8 , 14 , 16 , 23 , 24 met all criteria and were included in this systematic review ( Figure 1 ). The studies included 150 patients who underwent MPFLR with autograft and 193 with allograft ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 4 , 16 randomized patients to receive autograft or allograft. Kumar et al 14 allowed patients and their families to make a choice between autograft or allograft after discussion of risks and benefits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations